Novel anisotropic teleseismic body-wave tomography code AniTomo to illuminate heterogeneous anisotropic upper mantle: Part II - Application to data of passive seismic experiment LAPNET in northern Fennoscandia - Munzarová, Helena; Plomerová, Jaroslava; Kissling, Eduard; id_orcid:0 000-0001-9575-7951; Vecsey, Ludek; Babuška, Vladislav (Oxford University Press, 2018)
Seismic anisotropy provides a unique constraint on the past and present dynamics of the lithosphere and sublithospheric mantle. To contribute to studies of large-scale tectonic fabric, we have developed code AniTomo for regional anisotropic tomography. AniTomo allows us to invert simultaneously relative traveltime residuals of teleseismic P waves for 3-D distribution of isotropic-velocity perturbations and velocity anisotropy in the upper mantle. Weak hexagonal anisotropy with the symmetry axis oriented generally in 3-D is considered. The first application of novel code AniTomo to data from passive seismic experiment LAPNET results in a model of anisotropic velocities of the upper mantle beneath northern Fennoscandia. We have opted for northern Fennoscandia for the first application because it is a tectonically stable Precambrian region with a thick anisotropic mantle lithosphere without significant thermal heterogeneities. We carefully analyse the distribution of the rays to limit the fully anisotropic inversion only to the volume with the sufficient directional ray coverage. Capability of the given inversion setup to reveal large-scale anisotropic structures in the upper mantle is documented by a series of synthetic tests. The strongest anisotropy and the largest velocity perturbations concentrate at depths corresponding to the mantle lithosphere, while in deeper parts of the tomographic model, the lateral variations are insignificant. We delimit regions of laterally and vertically consistent anisotropy in the mantle–lithospheric part of the model. We attribute the retrieved domain-like anisotropic structure of the mantle lithosphere in northern Fennoscandia to preserved fossil fabrics of the Archean microplates, accreted during the Precambrian orogenic processes. ISSN:0956-540X ISSN:1365-246X